Pemanfaatan Rumput Laut Bagi Masyarakat Kecamatan Pontianak Utara Kota Pontianak - Belvi Vatria (Politeknik Negeri Pontianak, 2021)
Seaweed is one of the fishery commodities which can be used as a mainstay source of the national fisheries economy. Seaweed has long been known in Indonesia as a food, beverage, vegetable and traditional medicine ingredient. The target area for this community service program (PKM) is North Pontianak District, Pontianak City, which is also one of the tourism destinations for the equatorial monument in Indonesia. The partner group selected in this community service program (PKM) is the people of Batulayang Village, North Pontianak District, who are members of the village PKK group of 20 people divided into 5 small groups. The main objective of this PKM activity is to transfer seaweed utilization science and technology through training and assistance in processing food and beverages made from seaweed. In general, the results of this PKM activity run smoothly and thoroughly. After participating in this PKM activity, the training participants gained new skills about seaweed processing, how to make small-scale business feasibility, and how to market the seaweed products that have been produced. There are ten types of processed seaweed products, namely: seaweed brownies, seaweed pudding, seaweed drinks, seaweed bingke cake, seaweed ointment, seaweed sticks, seaweed crackers, seaweed lunkhead, seaweed jely, and sweets. seaweed. Increasing community skills in the use of seaweed is one of the efforts to support the community's economy and stretch tourism in the North Pontianak District. Key words: economy, livelihood, processing, empowerment